Tree of Life Groups for Children and Young People With Long-Term Medical Conditions and Their Parents Led by Pre-Qualification Psychology Staff - Kristina Soon; Caitlin Cook; Emily Golding; Eseoghene Obukohwo; India Browne; Morgan Baynes Zolkwer; Ramisa Hasan; Tripti Gureta; Georgia Setchell (Clinical Child Psychology and Psychiatry, 2026)
The Tree of Life group (Ncube, 2006) was designed to help children, young people (CYP), and adults who have experienced hard times or trauma to build resilience, restore hope, and connect with their strengths and social histories. A small number of publications have demonstrated a positive impact with CYP with long-term medical conditions (LTCs) (e.g., Casdagli et al., 2017) who are more likely to experience psychosocial challenges. In the context of increasing workforce pressures, the current study aimed to test if the positive results from previous studies could be replicated (1) with CYP’s who had been referred for psychological intervention rather than a self-selected group (2) with groups including CYP’s with different long-term conditions rather than the same condition (3) with pre-qualified psychology staff i.e. clinical psychology trainees, assistant psychologists and undergraduate psychology placement students as group facilitators (4) with parallel groups for parents of the CYP participants. Quantitative and qualitative feedback from CYP and parents was very positive providing support for running groups of CYP with pre-existing psychosocial challenges and different LTCs facilitated by pre-qualification staff. Feedback from pre-qualification facilitators highlighted the value of this learning opportunity and the importance of training and oversight by qualified staff.